PROGNOSTIC FACTORS IN HODGKIN LYMPHOMA - Annarosa Cuccaro; Francesca Bartolomei; Elisa Cupelli; Stefan Hohaus (Mediterranean Journal of Hematology and Infectious Diseases)
Hodgkin lymphoma (HL) is among the neoplastic diseases that has the best long-term outcome after cytotoxic treatment. Cure rates approach 80-90%, however, 15-20% of patients will be resistant to therapy (primary refractory) or relapse after treatment. Prognostic factors should help to stratify therapy according to the risk profile and identify patients at risk for failure. Significance of prognostic factors partly depends on the efficacy of the treatments administered, since new effective therapies can variably counterbalance the adverse effects of some unfavorable clinical determinants. As a consequence, some prognostic factors thought to be important in the past may become meaningless when modern successful therapies are used. Therefore, the value of prognostic factors has to be updated periodically, and compared to new emerging biomarkers. Besides the prognostic role of PET imaging, tissue and circulating biomarkers, as the number of tumor-infiltrating macrophages, cytokine and chemokine levels and profiling of circulating nucleic acids (DNA and microRNAs) have shown promise.